The In-Hospital Care of Patients With Peripheral Arterial Occlusive Disease - Decker, Josua A; Schwarz, Florian; Kroencke, Thomas J; Scheurig-Muenkler, Christian (Deutsches Ärzteblatt international, 2022)
Studies from Denmark and the USA have shown differences in treatment outcomes for patients with peripheral arterial occlusive disease (PAOD) between hospitals of different size and certification status. For Germany, it is not known whether certification as a specialist center for vascular diseases or hospital size is associated with differences in the primary treatment outcome.BACKGROUNDStudies from Denmark and the USA have shown differences in treatment outcomes for patients with peripheral arterial occlusive disease (PAOD) between hospitals of different size and certification status. For Germany, it is not known whether certification as a specialist center for vascular diseases or hospital size is associated with differences in the primary treatment outcome.Using data from the German Federal Statistical Office, all hospitalizations due to PAOD of Fontaine stage IIb or higher were included in our study and the hospitals were classified according to their size and certification status. PAOD stage, age, sex, and comorbidities were documented for each hospitalization. Univariate and multivariate logistic regressions were performed to identify independent variables that predict various treatment endpoints.METHODSUsing data from the German Federal Statistical Office, all hospitalizations due to PAOD of Fontaine stage IIb or higher were included in our study and the hospitals were classified according to their size and certification status. PAOD stage, age, sex, and comorbidities were documented for each hospitalization. Univariate and multivariate logistic regressions were performed to identify independent variables that predict various treatment endpoints.A total of 558 785 hospitalizations were included for analysis, of which 29% were in hospitals with certified vascular centers. In multivariate analysis, admissions to certified hospitals were associated with lower rates of major amputation (odds ratio [OR] 0.95, 95% confidence interval [0.92; 0.98], p = 0.003) and higher rates of minor amputation (OR 1.04 [1.01; 1.06], p = 0.004) with no difference observed in mortality (OR 0.99 [0.96; 1.03], p = 0.791). Admissions to larger hospitals were associated with more comorbidities, longer hospital stays, and higher rates of mortality and amputations.RESULTSA total of 558 785 hospitalizations were included for analysis, of which 29% were in hospitals with certified vascular centers. In multivariate analysis, admissions to certified hospitals were associated with lower rates of major amputation (odds ratio [OR] 0.95, 95% confidence interval [0.92; 0.98], p = 0.003) and higher rates of minor amputation (OR 1.04 [1.01; 1.06], p = 0.004) with no difference observed in mortality (OR 0.99 [0.96; 1.03], p = 0.791). Admissions to larger hospitals were associated with more comorbidities, longer hospital stays, and higher rates of mortality and amputations.Treatments in certified hospitals are associated with fewer major and more minor amputations. This may reflect intensification of therapy targeting preservation of functional limbs.CONCLUSIONTreatments in certified hospitals are associated with fewer major and more minor amputations. This may reflect intensification of therapy targeting preservation of functional limbs.